Assessment of the blood flow in kidneys of growth-restricted fetuses using quantitative three-dimensional power Doppler ultrasound - Pei-Yin Tsai; Chiung-Hsin Chang (Elsevier, 2018)
Objective: Fetuses with fetal growth restrictions have higher perinatal mortality rates than fetuses without fetal growth restrictions. Vascularization of the fetal kidney is crucial to fetal growth. Hence, we assessed blood flow and vascularization of fetal kidneys in non-growth-restricted as well as growth-restricted fetuses using quantitative three-dimensional power Doppler ultrasound. Materials and methods: We undertook a prospective study to evaluate the vascular indices of fetal kidneys; i.e., the vascularization index, flow index and vascularization-flow index, in growth-restricted and non-growth-restricted fetuses using three-dimensional power Doppler ultrasound and quantitative three-dimensional histogram analysis. All fetuses from 20 to 40 weeks of gestation were singletons with a normal pregnancy and were followed up to delivery. Results: In total, 209 fetuses without fetal growth restriction and 50 fetuses with fetal growth restriction were included. Our results showed the fetal renal vascularization index, flow index, and vascularization-flow index evaluated by three-dimensional power Doppler ultrasound can differentiate fetuses with fetal growth restriction from fetuses without fetal growth restriction. Conclusion: The fetal renal vascularization index, flow index, and vascularization-flow index measured by three-dimensional power Doppler ultrasound can be applied to prenatally detect fetal growth restriction. Our data support assessment of the fetal renal vascularization index, flow index, and vascularization-flow index using three-dimensional power Doppler ultrasound as a useful test for detecting fetuses with fetal growth restriction. Keywords: Fetal growth restriction (FGR), Kidney, Vascularization index (VI), Flow index (FI), Vascularization-flow index (VFI)